A multi-criteria decision support system for the assessment of cities based on air quality indicators. (14th June 2023) - Garg, Rakesh; Raheja, Supriya; Gupta, Aakash; Munjal, Geetika
A deterministic decision support system is developed for the assessment and ranking of various cities based on the air quality indicators in this research. The present study models such assessment of cities as a multi-criteria decision-making (MCDM) problem due to the involvement of multiple air quality indicators. Further, to solve the present assessment problem, a hybrid MCDM approach, namely, entropy-evaluation based on distance from average solution (EDAS-E) is implemented by integrating two well-known approaches such as Shannon entropy and evaluation based on distance from average solution (EDAS). Shannon entropy approach is used to calculate the priority weights of the air quality indicators whereas the EDAS method is used to get the comprehensive ranking of the cities based on the identified air quality indicators.